2023
DOI: 10.1108/srj-09-2022-0364
|View full text |Cite
|
Sign up to set email alerts
|

Does CSR affect tax avoidance? Moderating role of political connections in Bangladesh banking sector

Md. Harun Ur Rashid,
Farhana Begum,
Syed Zabid Hossain
et al.

Abstract: Purpose This study aims to investigate whether socially responsible businesses with corporate social expenditure are less prone to engaging in tax avoidance. The study also examines whether political connections moderate the association between corporate social responsibility (CSR) and tax avoidance. Design/methodology/approach The study uses ordinary least squares to analyse the panel data of all 30 listed banks on the Dhaka Stock Exchange covering 2012 to 2020. The study uses a set of alternative variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Rashid et al. (2023) found that higher CSR expenditure can reduce corporate tax avoidance, but political ties reduce the contribution of CSR to tax evasion.…”
Section: Literature Review On the Current State Of The Fieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Rashid et al. (2023) found that higher CSR expenditure can reduce corporate tax avoidance, but political ties reduce the contribution of CSR to tax evasion.…”
Section: Literature Review On the Current State Of The Fieldmentioning
confidence: 99%
“…Sound governance incentivises taxpayers to correctly declare their taxable income (Murshed and Saadat, 2018) and leads to lower tax evasion in developing countries (Rashid et al. , 2023).…”
Section: Literature Review On the Current State Of The Fieldmentioning
confidence: 99%
See 3 more Smart Citations